(untitled) (UNED Research Journal, 2020)
Introduction: Chlorophyll Fluorescence (Fv/Fm) detects damage in photosystem II (PSII) in plants exposed to stress (biotic and/or abiotic). Objective: In this context, Fv/Fm for the diagnosis of the effect of N deficiency and light in tomato plants (Solanum lycopersicum) was evaluated. Methods: We used the software R to analyze data from an experiment consisted of two light treatments (high and low) and two Hoagland nutritive solutions (N deficiency: (-)N; and complete solution: C). Twenty tomato plants within the two light treatments, with two nutrient levels ((-)N and C) were used. For four weeks, weekly measurements for height (H), leaf number (NL), and Fv/Fm were made. On the fourth week, the dry mass partitioning (root: RMR; stem: SMR; and leaves: LMR) and chlorophyll concentration (a, b, a/b, and total) was measured. Results: We found statistically significant differences between treatments for H, NL and Fv/Fm (KW> 14,5, g.l.= 3,76, P<0,01), but no differences for chlorophyll concentration (F<2,2; g.l.=1, 16, P>0,05). In both light conditions it was higher LMR in C treatment, but with lower RMR compared to (-)N. Statistically significant correlations (% Spearman, P<0,05) between Fv/Fm and LMR, RMR, and SMR (-76%, 69%, and 37%, respectively) were found. Conclusion: Overall, we can emphasize that the Fv/Fm is a sensitive variable to the stress caused by nitrogen and light deficiency, whose progress of stress time-course can assess. Finally, Fv/Fm proved to be an indicator of the dry mass partition of stress induced by N deficiency and could be implemented as diagnostic in breeding programs.